PENANGANAN MAHASISWA DEPRESI DENGAN KONSELING KOGNITIF: : SEBUAH STUDI KASUS - Seralarat, Kornelis; Reresi, Marsianus; Rahawarin, Bernard A. (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2019)
Students who are depressed will have problem to concentrate to finish their studies. Depression is one of mood disorders due to intense sadness, hopeless and withdrawal from others which disrupts daily activities and behavior. The purpose of this study is to analyze and explain the usefulness of Cognitive Therapy in dealing with depressed students. Cognitive therapy is a process of treatment to help client to correct his faulty belief and thinking that can impact on client‟s emotion and behavior. This study uses a qualitative method. The type of research used is a Case Study. The subjects were several students who showed symptoms of depression.